Establishment and Operation of Wartime Health Care System in North Korea during the Korean War and Support from the Korean Society in Yanbian - Mira MOON (Uisahak, 2020)
North Korea's health care system during the Korean War has a significant meaning in North Korean medical history and is also an appropriate research topic for understanding North Korea's wartime system. However, previous studies on North Korean medical history has been focused on before and after the war. This study traces the formation and operation of North Korea's wartime health system to fill the gap in the literature, aiming to identify that the support of the North Korean community in China's Yanbian community was key to North Korea's wartime health system. North Korea reorganized its health care system, centered on the military, such as establishing field hospitals concurrently with the outbreak of the war. However, as time went on, the North Korean health care project began to put an emphasis on protecting the lives and health of the civilians behind the frontline. In addition to the primary need to prevent infectious diseases, the hygiene and prevention project functioned as a means to control and mobilize the public by emphasizing broad public participation. Although North Korea tried to meet the demand for a large medical personnel through short-term training, medical personnel were always in short supply during the war. During the war, it was the Korean society in Yanbian that replenished medical personnel in North Korea and provided a space for a relatively stable hospital operation. Numerous Koreans in Yanbian participated in the Korean War as nurses, paramedic staff, transfusion donors, and army surgeons for North Korea. Such large-scale participation of medical personnel in Yanbian was based on the long-established medical exchanges between Yanbian and North Korea. Koreans in Yanbian also accommodated North Korean wounded, refugees, and war orphans and provided various medical assistance to them. During the war, Yanbian was a “secure rear” capable of performing medical actions that could not be done in North Korea. This study has confirmed that North Korea's current participation in public health projects, which is a characteristic of its health care sector, has its origins in the Korean War. Moreover, it demonstrates that North Korea's medical history needs to be viewed from an East Asian perspective, including the Korean society in Yanbian, rather than a national-only perspective. The application of this view to the analysis of North Korean’s health care system in other historical periods would facilitate richer discussions.